Divorcio y su incidencia en el estado emocional de un adolescente de 15 años de edad del cantón de Ventanas - Ortiz Almea, Victor Jefferson (2022)
Divorce is the breakdown of the couple's marital relationship that occurs when the couple decides to end their relationship for different reasons that may be the lack of understanding of the couple, adultery, among others. In which if the two members of the couple end the relationship, they would carry out a faster and more timely legal process, but if this is not the case, they would have to move to a more complex legal environment that would determine, through negotiation, factors such as custody and food. in the case of having children, possession of properties in case they were acquired in the marriage, among others. During this process it is notable that the family goes through several changes that emotionally affect the children; although it is not yet clear if what affects the children is the breakup, that is, the divorce as such, or the social impositions of what family means, in addition to the fact that each child interprets it and affects them differently, causing a series of symptoms and unhealthy emotions that affect your well-being.